Micellar Enhanced Three-Dimensional Excitation-Emission Matrix Fluorescence for Rapid Determination of Antihypertensives in Human Plasma with Aid of Second-Order Calibration Methods - Hai-Yan Fu; He-Dong Li; Chuang Ni; Tian-Ming Yang; Yao Fan; Hao Zhang; Ji Yang; Lin Chen; Yuan-Bin She (Journal of Spectroscopy)
A highly sensitive three-dimensional excitation-emission fluorescence method was proposed to determine antihypertensives including valsartan and amlodipine besylate in human plasma with the aid of second-order calibration methods based on parallel factor analysis (PARAFAC) and alternating trilinear decomposition (ATLD) algorithms. Antihypertensives with weak fluorescent can be transformed into a strong fluorescent property by changing microenvironment in samples using micellar enhanced surfactant. Both the adopted algorithms with second-order advantage can improve the resolution and directly attain antihypertensives concentration even in the presence of potential strong intrinsic fluorescence from human plasma. The satisfactory results can be achieved for valsartan and amlodipine besylate in complicated human plasma. Furthermore, some statistical parameters and figures of merit were evaluated to investigate the performance of the proposed method, and the accuracy and precision of the proposed method were also validated by the elliptical joint confidence region (EJCR) test and repeatability analysis of intraday and interday assay. The proposed method could not only light a new avenue to directly determine valsartan or amlodipine besylate in human plasma, but also hold great potential to be extended as a promising alternative for more practical applications in the determination of weak fluorescent drugs.